S125 Ly6Chi circulating monocytes direct alternatively activated, pro-fibrotic, lung macrophage regulation of pulmonary fibrosis. (16th November 2010) - Gibbons, M A; MacKinnon, A C; Ramachandran, P; Duffin, R; Dhaliwal, K; Haslett, C; Howie, S E M; Simpson, A J; Hirani, N; Gauldie, J; Iredale, J P; Sethi, T; et al.
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) remains one of the few respiratory conditions for which there are no effective therapies. The role of monocytes and macrophages in IPF has been disputed as anti-inflammatory therapies produce questionable benefit. Corticosteroids, however, actually induce an alternatively activated, pro-fibrotic, macrophage phenotype. We sought to determine whether monocytes and macrophages play a role in disease pathogenesis in an attempt to explain why current hypotheses and anti-inflammatory therapies have produced limited clinical benefit despite years of research. Methods: Using multiple in vivo depletional strategies, backed up by an adoptive transfer technique, we extensively investigated the role of monocytes and macrophages during lung fibrogenesis. We performed studies on samples from patients with IPF in an attempt to determine the translational importance of our findings. Results: Depletion of lung macrophages during fibrogenesis reduced pulmonary fibrosis as measured by lung collagen (p=0.0079), fibrosis score (p=0.0051), and qPCR for surrogate markers of fibrosis Col1 (p=0.0083) and a-smooth muscle actin (p=0.0349). There was an associated reduction in expression of markers of alternative macrophage activation, Ym1 (p=0.0179), and Arginase1 . This reduction was confirmed by immunohistochemistry (IHC) for Ym1 (p=0.0233). IHC on lung macrophages from patients with IPF demonstrated the novel finding of expression of the human alternative macrophage marker CD163. Depletion of Ly6C hi circulating monocytes reduced pulmonary fibrosis (p=0.0052). Adoptive transfer of Ly6C hi BMDMS during fibrogenesis exacerbated pulmonary fibrosis (p=0.0304). Furthermore, depletion of circulating Ly6C hi monocytes lead to a subsequent reduction in the number of Ym1-positive alternatively activated lung macrophages (p=0.0310) with a concomitant reduction in the expression of Ym1 and Arginase1 . Conclusions: We have demonstrated that monocytes and macrophages do modulate pulmonary fibrosis and suggest that Ly6C hi monocytes (possible fibrocyte precursors) are precursors of alternatively activated, pro-fibrotic, lung macrophages. These findings could link the 'inflammatory' and aberrant wound healing hypotheses and explain the lack of effectiveness of corticosteroids in treating IPF. By enhancing our understanding of the pathogenesis of this dreadful disease, our results may enable new therapeutic targets to be developed, facilitate targeted cell-based therapy, and bring hope to one of the longstanding enigmas of respiratory medicine.